If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 + -1y = 20 Solving 33 + -1y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -1y = 20 + -33 Combine like terms: 33 + -33 = 0 0 + -1y = 20 + -33 -1y = 20 + -33 Combine like terms: 20 + -33 = -13 -1y = -13 Divide each side by '-1'. y = 13 Simplifying y = 13
| 40+3x=(5x-10) | | .50x+.25(70)=37.5 | | x-(21)=9 | | -9k=126 | | 22+y=25 | | -7x^4y(5x^2+9x^6y^3-3y^3)= | | cos(2x)*cos(4x)= | | -9=126 | | 1.2-n+3.4=10 | | 2x-53=17 | | 2=t(28-4.9t) | | 0.25x+.05(6-x)=.10(-29) | | 3n-10=56 | | 3x^2+3y^2+18x-42y+162=0 | | 42=4x+6y | | (2x^3)+16=0 | | 4y-4+y+28=5+5y+25-3y | | 5(n-18)=10 | | p=10-4y+y^2 | | x^2-72x+100=0 | | 36x^3-15x^2+84x-35=0 | | 9x+12=5x+8 | | 2=t(20-4.9t) | | 6x+7=7x+6 | | 8x-52=2x+14 | | x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 | | (7+3i)-(2+3i)= | | 3y+3x-2=7 | | 1n+9n-10-3= | | 7(9x-3)=4(3x+2) |